2023
DOI: 10.1542/peds.2022-059938
|View full text |Cite
|
Sign up to set email alerts
|

Bundled Care to Reduce Sepsis Mortality: The Improving Pediatric Sepsis Outcomes (IPSO) Collaborative

Abstract: OBJECTIVES: We sought to improve utilization of a sepsis care bundle and decrease 3- and 30- day sepsis-attributable mortality, as well as determine which care elements of a sepsis bundle are associated with improved outcomes. METHODS: Children’s Hospital Association formed a QI collaborative to Improve Pediatric Sepsis Outcomes (IPSO) (January 2017–March 2020 analyzed here). IPSO Suspected Sepsis (ISS) patients were those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 34 Similarly, a recently published IPSO interim analysis found that bundle compliant care was associated with significant reduction in mortality. 40 These results suggest that all bundled-care elements are likely important rather than one singular intervention, which is also emphasized in the 2020 Pediatric Surviving Sepsis Campaign guidelines. 20 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“… 34 Similarly, a recently published IPSO interim analysis found that bundle compliant care was associated with significant reduction in mortality. 40 These results suggest that all bundled-care elements are likely important rather than one singular intervention, which is also emphasized in the 2020 Pediatric Surviving Sepsis Campaign guidelines. 20 …”
Section: Discussionmentioning
confidence: 86%
“…An investigation of a 1-hour sepsis bundle implementation following the New York State mandate found that completion of the entire bundle (obtaining blood cultures, administering broad-spectrum antibiotics, and a 20 mL/kg IV fluid bolus) within 1 hour was associated with lower risk-adjusted odds of in-hospital mortality (OR, 0.59; 95% CI, 0.38-0.93), whereas administration of antibiotics in isolation within 1 hour was not (OR, 0.78; 95% CI, 0.55-1.12) . Similarly, a recently published IPSO interim analysis found that bundle compliant care was associated with significant reduction in mortality . These results suggest that all bundled-care elements are likely important rather than one singular intervention, which is also emphasized in the 2020 Pediatric Surviving Sepsis Campaign guidelines …”
Section: Discussionmentioning
confidence: 94%